Glycemic outcomes related to depression in adults with type 1 diabetes. (July 2021) - Egbuonu, Ifeoma; Trief, Paula M; Roe, Cheryl; Weinstock, Ruth S
Glycemic outcomes of adults with type 1 diabetes may be affected by depression. Our aim was to compare outcomes of "depressed" (Patient Health Questionnaire-9 ⩾ 10, N = 83) to "not-depressed" matched control (Patient Health Questionnaire-2 < 3, N = 166) adults with type 1 diabetes with objective measures. The depressed group had poorer blood glucose control and, for those with glucose meter downloads, fewer glucose tests/day. The groups did not differ on glucose variability or episodes of hypoglycemia. Depression in adults with type 1 diabetes is associated with poorer glycemic control and less blood glucose monitoring. Future research should examine whether treatment of depression results in better self-care and glycemic outcomes.